Accounting for Startup: As scary as Freddy - Sudibyo, Yudha Aryo; Puspasari, Novita (Jurnal Akuntansi dan Bisnis, 2021)
Indonesia has enormous numbers of startup companies which grow rapidly in the past four years. However, many startups fail in the first year due to their lack of business sustainability. The problem for most startups is measurement. In order to measure its growth and efficiency, startup companies need accounting. This study aims to explore and gain an in-depth understanding from the view of startup companies on accounting. With a qualitative approach, this study used the ZMET (Zaltman Metaphor Elicitation Technique) method to dig information from seven startup companies as research participants. Using ZMET’s projective techniques through image metaphors, the study has identified thirteen important constructs which describe a mental model of startup companies toward accounting. Connections among constructs are described in the consensus map, which explains three main themes of this study’s findings: mental block of accounting, accounting as a tool, and ultimate startup goal. This study has theoretical contributions, practical contributions, and methodological contributions.Indonesia memiliki sejumlah besar perusahaan startup yang tumbuh pesat dalam empat tahun terakhir. Namun, banyak startup gagal pada tahun pertama karena kurangnya keberlanjutan bisnis. Masalah yang banyak dihadapi oleh startup adalah pengukuran. Akuntansi diperlukan oleh startup untuk mengukur pertumbuhan dan efisiensinya. Penelitian ini bertujuan untuk mengeksplorasi dan memperoleh pemahaman mendalam dari perusahaan startup mengenai akuntansi. Studi ini menggunakan pendekatan kualitatif, metode ZMET (Zaltman Metaphor Elicitation Technique) digunakan untuk menggali informasi dari tujuh perusahaan startup yang dijadikan partisipan. Proyeksi ZMET mengidentifikasi tiga belas konstruk penting yang menggambarkan model mental perusahaan startup terhadap akuntansi. Hubungan antar konstruk digambarkan melalui consensus map yang menjelaskan tiga temuan penting yaitu mental block akuntansi, akuntansi sebagai alat dan tujuan akhir startup. Penelitian ini mempunyai kontribusi terhadap teori, praktik dan metodologi.